(3SjGSGJ JSYjQ GdOhGA (B/s - (3GdUjQaj, eMeOs ((3GdGScfOQjI(B: s (3OGQ GdhaGA dOjfG ddWHGYI hGdfTQ(B, s, 2007)
(3jVe GdEWGQ GdfXQj deTcdI GdHMK, GdSjGSI GdSYQjI dLeghQjI eUQ GdYQHjI, GdYhGed GdeDKQI Ydi GdSjGSI GdSYQjI GdOhGFjI HLeghQjI eUQ GdYQHjI, GdfJGFL hGdJhUjGJs
Keywords: (3GdCOhjI(B-(3CSYGQs; (3GdCSYGQ(B- (3SjGSIs